Visiting experiences and behavioural types in cultural audiences: an analysis of two museums in Lisbon - Costa, P. (2016)
Audiences of cultural events are subject to diverse kinds of experiences in their exercise, which de termine the structure of their to structure their consumption practices and cultural habits. Mapping and analysing visitors’ experiences and their visiting styles is thus fundamental tocenhance museums’ offer appeal. Drawing on a conceptual framework which identifies four main kinds of experiences in cultural practices - (i) intellectual experience (ii) emotional experience; (iii) social experience; and (iv) recreational experience, the audiences of two museums in the city of Lisbon (Fado Museum and Puppets Museum) are analysed in this paper. Considering a typology of diverse audience categories (permanent collection, temporary exhibitions, other events), a detailed study of the assessment of different experiences is pursued, with the aim to confront and identify relevant discriminant categories such as socio-demographic characteristics (e.g. age, gender, qualifications, professional status, nationality, residence, previous artistic practices) and cultural habits (considering their visits to other cultural facilities and events). Considering the conclusions, some policy-oriented recommendations from this analysis are discussed.